A chloroacetate based ratiometric fluorescent probe for cysteine detection in biosystems. Issue 44 (31st October 2019) - Liu, Zhengkun; Wang, Qianqian; Wang, Hao; Su, Wenting; Dong, Shouliang
Graphical abstract: Highlights: Four chloroacetate based fluorescent probes were synthesized for a comparative study. H4 displayed great ratiometric property and selectivity for cysteine. H4 was applied for real-time cysteine imaging in HeLa cells. Abstract: The specific detection of cysteine (Cys) over homocysteine (Hcy), glutathione (GSH) and other amino acids is of great significance for studying its biological functions as well as for the diagnosis of related diseases. Chloroacetyl group was often used as a reaction site for cysteine fluorescent probes for its sensitivity and selectivity. However, high background fluorescence and low stability are common problems encountered by such probes. Here, four chloroacetyl group based fluorescent probes (C1, C2, C3, andH4 ) was synthesized for a comparative study. We found that the inefficient quenching ability of chloroacetyl group turned into an advantage when connected with a ratiometric fluorophore. With the modification of chloroacetyl group, probeH4 displayed excellent ratiometric property and great selectivity for Cys, the stability was also improved. Additionally, the probe was successfully applied for quantitative detection of Cys in fetal bovine serum and real-time imaging in living HeLa cells with low toxicity.